Question #23896

2n^4-9n^2+=0

Expert's answer

2n^4-9n^2=0

let t=n^2 then we have

2t^2-9t=0

we can rewrite it as

t(2t-9)=0

then t=0 or t=9/2

so, returning to initial denotations, we get n^2=0 or n^2=9/2n=0 or n=-3/sqrt(2) or n=3/sqrt(2)

Thus, the answer is n=0; +-3/sqrt(2)

let t=n^2 then we have

2t^2-9t=0

we can rewrite it as

t(2t-9)=0

then t=0 or t=9/2

so, returning to initial denotations, we get n^2=0 or n^2=9/2n=0 or n=-3/sqrt(2) or n=3/sqrt(2)

Thus, the answer is n=0; +-3/sqrt(2)

## Comments

## Leave a comment